Saving babies? : the consequences of newborn genetic screening - Timmermans, Stefan, 1968-; Buchbinder, Mara (Chicago ; London : The University of Chicago Press, 2013)
It has been close to six decades since Watson and Crick discovered the structure of DNA and more than ten years since the human genome was decoded. Today, through the collection and analysis of a small blood sample, every baby born in the United States is screened for more than fifty genetic disorders. Though the early-detection of these abnormalities can potentially save lives, the test also has a high percentage of false positives, inaccurate results that can take a brutal emotional toll on parents before they are corrected. Now some doctors are questioning whether the benefits of these screenings outweigh the stress and pain they sometimes produce. In this book the authors evaluate the consequences and benefits of state-mandated newborn screening, and the larger policy questions they raise about the inherent inequalities in American medical care that limit the effectiveness of this potentially lifesaving technology. Drawing on observations and interviews with families, doctors, and policy actors, the authors offer this ethnographic study of how parents and geneticists resolve the many uncertainties in screening newborns.
Introduction: the consequences of newborn screening -- The expansion of newborn screening -- Patients-in-waiting -- Shifting disease ontologies -- Is my baby normal? -- The limits of prevention -- Does expanded newborn screening save lives? -- Conclusion: the future of expanded newborn screening.
Includes bibliographical references and index.
Keywords: Newborn infants -- Medical examinations -- Social aspects -- United States; Newborn infants -- Diseases -- Diagnosis -- Social aspects; Genetic screening -- Social aspects -- United States; Medical screening -- Social aspects -- United States; Genetic Testing; Neonatal Screening; Genetic Diseases, Inborn; Infant, Newborn, Diseases; Infant, Newborn; 44.02 philosophy and ethics of medicine; Genetic screening -- Social aspects; Medical screening -- Social aspects; United States